European Society for Paediatric Gastroenterology, Hepatology and Nutrition Guidelines for the Evaluation and Treatment of Gastrointestinal and Nutritional Complications in Children With Neurological Impairment. Issue 2 (August 2017) - Romano, Claudio; van Wynckel, Myriam; Hulst, Jessie; Broekaert, Ilse; Bronsky, Jiri; Dall'Oglio, Luigi; Mis, Nataša F.; Hojsak, Iva; Orel, Rok; Papadopoulou, Alexandra; Schaeppi, Michela; Thapar, Nikhil; et al.
ABSTRACT: Objectives: Feeding difficulties are frequent in children with neurological impairments and can be associated with undernutrition, growth failure, micronutrients deficiencies, osteopenia, and nutritional comorbidities. Gastrointestinal problems including gastroesophageal reflux disease, constipation, and dysphagia are also frequent in this population and affect quality of life and nutritional status. There is currently a lack of a systematic approach to the care of these patients. With this report, European Society of Gastroenterology, Hepatology and Nutrition aims to develop uniform guidelines for the management of the gastroenterological and nutritional problems in children with neurological impairment. Methods: Thirty-one clinical questions addressing the diagnosis, treatment, and prognosis of common gastrointestinal and nutritional problems in neurological impaired children were formulated. Questions aimed to assess the nutritional management including nutritional status, identifying undernutrition, monitoring nutritional status, and defining nutritional requirements; to classify gastrointestinal issues including oropharyngeal dysfunctions, motor and sensory function, gastroesophageal reflux disease, and constipation; to evaluate the indications for nutritional rehabilitation including enteral feeding and percutaneous gastrostomy/jejunostomy; to define indications for surgical interventions (eg, Nissen Fundoplication, esophagogastric disconnection); and finally to consider ethical issues related to digestive and nutritional problems in the severely neurologically impaired children. A systematic literature search was performed from 1980 to October 2015 using MEDLINE. The approach of the Grading of Recommendations Assessment, Development, and Evaluation was applied to evaluate the outcomes. During 2 consensus meetings, all recommendations were discussed and finalized. The group members voted on each recommendation using the nominal voting technique. Expert opinion was applied to support the recommendations where no randomized controlled trials were available. Abstract : Supplemental Digital Content is available in the text